The effects of deoxidation practice on the quality of thin foil low-carbon steel - Pereira Batista R.; Augusto Martins A.; Costa e Silva A.L.V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In converter steelmaking of AISI 1006 steel for thin foil products, two tapping practices are used with respect to deoxidation: silicon and manganese additions during tapping and aluminum deoxidation after complete tapping (“semikilled practice”) and aluminum deoxidation during tapping, “fully killed practice”. There is a perception that the semikilled practice may be more economical and result in the same quality as the fully killed practice. In this work, the effects of the tapping practice on steel quality and cost variables were evaluated for thin foils of AISI 1006 steel. Oxygen and aluminum content, aluminum and ferro-alloy yield, the type of alumina inclusions formed, and the quality of the steel during thin foil rolling were evaluated and compared. It is shown that the fully killed practice leads to less reoxidation from slag, lower soluble oxygen, and lower total oxygen at the caster as well as better morphology of the remaining alumina inclusions than the semi-killed practice. Thus, the higher quality of the steel produced via the fully killed tapping deoxidation practice when compared with semi-killed tapping is demonstrated. It is also shown that a complete cost evaluation favors this practice in the case of products rolled for tin foil production.